2020
DOI: 10.1007/s11356-020-08069-9
|View full text |Cite
|
Sign up to set email alerts
|

An innovative approach for the simultaneous quantitative screening of organic plastic additives in complex matrices in marine coastal areas

Abstract: Aiming the simultaneous determination of widely used organic plastic additives in complex marine matrices, this work proposes a fast and "green" analytical protocol based on quick, easy, cheap, effective, rugged, and safe (QuEChERS) technology. The validation of this innovative method on real matrices (i.e., sediments, mussel, fish, and Posidonia oceanica) indicated a general good performance in all of them for phthalate esters (PAEs), with low blank levels and average method recoveries varying from 54 ± 11 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Nontarget screening aims to obtain as much information as possible from environmental samples; thus, an efficient, manageable, and powerful sample pretreatment method is a key step in the process of sample analysis. Recently, a simple and popular sample preparation methodology, i.e., QuEchERS technique, has been widely used in the extraction of many toxic and harmful pollutants including OPEs in various media . In the process, ACN is a preferential extractant due to the good protein precipitation effect, excellent compatibility, and low solubility .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nontarget screening aims to obtain as much information as possible from environmental samples; thus, an efficient, manageable, and powerful sample pretreatment method is a key step in the process of sample analysis. Recently, a simple and popular sample preparation methodology, i.e., QuEchERS technique, has been widely used in the extraction of many toxic and harmful pollutants including OPEs in various media . In the process, ACN is a preferential extractant due to the good protein precipitation effect, excellent compatibility, and low solubility .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a simple and popular sample preparation methodology, i.e., QuEchERS technique, has been widely used in the extraction of many toxic and harmful pollutants including OPEs in various media. 37 In the process, ACN is a preferential extractant due to the good protein precipitation effect, excellent compatibility, and low solubility. 38 Although the QuEChERS method with ACN as the extraction solvent has been reported to be successfully used for OPE analysis in the environmental matrices (e.g., sediment) and food (e.g., dairy products) and fish samples using LC-MS or GC-MS, analysis of trace OPEs as well as unknown OPEs in biotic samples (e.g., fish) remains a challenge using HRMS in terms of accuracy and precision.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sánchez-Ávila et al, [65] detected levels of DEHP in mussels from three out of five coastal and estuarine sites studied in the Cantabrian Sea (Spain). Furthermore, Castro-Jiménez & Ratola [66] detected levels of DEHP in both wild and commercial mussels, levels of BzBP in wild mussels and levels of DEP in fish from the Mediterranean Sea. Furthermore, boys showed higher urinary levels of MEHP (DEHP metabolite) than girls from the present study, however, we have not found an explanation for this association.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is little information on determining these compounds or the occurrence of OP diesters in living organisms. This information should therefore be extended to seafood as it is a very common dietary exposure route to these contaminants for humans [ 23 ].…”
Section: Introductionmentioning
confidence: 99%